2020
DOI: 10.1111/clr.13685
|View full text |Cite
|
Sign up to set email alerts
|

Thermal effects of various drill materials during implant site preparation—Ceramic vs. stainless steel drills: A comparative in vitro study in a standardised bovine bone model

Abstract: Objectives The aim of this study was to evaluate thermal effects of ceramic and metal implant drills during implant site preparation using a standardised bovine model. Material and Methods A total of 320 automated intermittent osteotomies of 10‐ and 16‐mm drilling depths were performed using zirconium dioxide‐based and stainless steel drills. Various drill diameters (2.0/ 2.2, 2.8, 3.5, 4.2 mm ∅) and different cooling methods (without/ with external saline irrigation) were investigated at room temperature (21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 88 publications
(195 reference statements)
1
33
0
Order By: Relevance
“…In actual clinical trials, a saline solution is injected to reduce the heat generation of bone tissue. 19 In addition, the initial stability of the implant can be maintained through stepwise torque placement rather than by applying continuous force.18,19 Though, in this study, the output torque was measured in a laboratory environment, which is different from the clinical placement environment. To calculate more torque values, additional experiments with various torque values of implants from other companies are required.…”
Section: Discussionmentioning
confidence: 99%
“…In actual clinical trials, a saline solution is injected to reduce the heat generation of bone tissue. 19 In addition, the initial stability of the implant can be maintained through stepwise torque placement rather than by applying continuous force.18,19 Though, in this study, the output torque was measured in a laboratory environment, which is different from the clinical placement environment. To calculate more torque values, additional experiments with various torque values of implants from other companies are required.…”
Section: Discussionmentioning
confidence: 99%
“…Low torque during implant placement provides insufficient torque to obtain initial fixation of the implant, and excessive torque may generate heat in the surrounding bone tissue, leading to bone necrosis. 15 16 17 Neugebauer et al 1 reported the possibility that the implant may fail if the output torque is more than 35 Ncm during implant placement and that the placement torque and implant stability are related. Strietzel et al 18 reported that a high output torque could lead to a high bone resorption rate.…”
Section: Discussionmentioning
confidence: 99%
“…For vertical dislocation measurement and program control, an external linear potentiometer (Linear Potentiometer 600 Series, Type 9615R5.1KL2.0, BEI Sensors, Goleta, CA) was used. In correspondence with previous investigations, 29–31,35 two drilling sequences (10 and 16 mm) with predefined parameters (dwell time, depth control, and drilling/withdrawing feed rate) were programmed. Ten millimeters drilling sequences were programmed with 27.6 s (drilling time 17.3 s, withdrawing time 10.3 s) and 16‐mm drilling procedures with 43.5 s (drilling time 27.1 s, withdrawing time 16.4 s).…”
Section: Methodsmentioning
confidence: 99%
“…The computer‐based temperature measurement system (SHTM‐Temperature Measurement System, Center for Medical Physics and Biomedical Engineering, Medical University of Vienna, Austria) was software‐controlled (DASYLab® Software 5.0, Measurement Computing Corporation, Norton, MA) and included an ADC‐converter (Analog‐to‐digital‐converter; NI DAQCard™‐6062 E, National Instruments™, Austin, TX) and a measurement amplifier (SHU‐Measurement Amplifier, Center for Medical Physics and Biomedical Engineering, Medical University of Vienna, Austria). For obtaining real‐time temperature values in multiple depths simultaneously, NTC‐detected signals were converted after calibration against traceable standards 29–31,35 . The temperature data recording started 10 s before the surgical procedure and ended 25 s after the withdrawing process.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation